Association of serum MMP9 with adverse features of plaque progression in patients with chronic coronary syndrome (CCS). (3rd October 2022) - Caselli, C; Ragusa, R; Di Giorgi, N; Lorenzoni, V; Buechel, R R; Teresinska, A; Pizzi, M N; Roque, A; Poddighe, R; Knuuti, J; Parodi, O; Pelosi, G; et al.
Abstract: Background: Previous studies have demonstrated that MMP-9 may be a predictor of atherosclerotic plaque instability and future adverse cardiovascular events, but longitudinal data on the association between MMP9 and coronary disease progression are lacking. Purpose: This study is aimed at investigating whether MMP9 is associated with atherosclerotic plaque progression. Methods: MMP9 serum levels were measured in stable patients with chronic coronary syndrome (CCS) undergoing coronary computed tomography angiography at baseline and after a period of 6.5±1.1 years of follow up to assess progression of Total, Fibrous, Fibro-fatty, Necrotic Core, and Dense Calcium plaque volume (PV). The relationship of serum MMP9 with plaque progression was assessed using linear regression analysis, adjusting for clinical variables including, age, sex, risk factors, medical therapy, LDL-C, TG/HDL-C ratio, hs-CRP, and the presence of obstructive CAD (>50% coronary stenosis in at least one major coronary vessels). Results: A total of 157 patients (58±8 years of age; 66% males) were included in the analysis, with median MMP9 values of 135±186 mg/dL (mean ± SD). Annual changes of Total, Fibrous-Fatty and Necrotic Core PV were significantly different across MMP9 tertiles (Figure 1). Multivariable linear regression analysis demonstrated a positive association between serum levels of MMP9 and annual change of Total and Necrotic Core PV (Figure 1). Conclusion: Among patients with CCS, MMP9 serum levels were an independent predictor of progression of coronary plaque burden and, in particular, of adverse plaque features, such as Necrotic Core PV. This association was robust and independent from baseline traditional cardiovascular risk factors and medications, supporting for MMP9 a role as a novel marker of residual coronary risk. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020 - Project "Simulation Modeling of coronary ARTery disease: a tool for clinical decision support–SMARTool"